Improving children’s visual health by integrating motor imagery training into physical education classes - Zhou, Sheng; Ren, Yuanyuan; Ma, Sien; Zhang, Meng; Yin, Rongbin (Frontiers in Psychology, 2025)
IntroductionMyopia threatens healthy physical and mental development in children. Research suggests that motor imagery training could serve as a non-invasive and cost-effective non-pharmacological intervention to address myopia and promote health. Therefore, this study examined the effect of incorporating motor imagery training into physical education classes on children’s visual health.MethodsA 16-week intervention was conducted. The participants were 154 children divided into four groups: three experimental and one control. Group 1 performed motor imagery exercises with a visual target moving near and far, Group 2 performed physical activity imagery exercises combined with visual tasks, and Group 3 performed physical activity combined with visual tasks.ResultsAfter the intervention, kinetic visual acuity (p < 0.05), accommodation facility (p < 0.01), and uncorrected distance visual acuity (p < 0.01) improved significantly in all experimental groups. Moreover, Groups 1 and 2 showed significant improvements in cognitive specific motor imagery abilities (p < 0.05). There were significant differences in kinetic visual acuity (F = 2.994, p = 0.033, η2 = 0.056), accommodation facility (F = 8.533, p < 0.001, η2 = 0.146), right-eye uncorrected distance visual acuity (F = 5.550, p = 0.001, η2 = 0.100) and left-eye uncorrected distance visual acuity (F = 2.667, p = 0.050, η2 = 0.051) among the four groups.ConclusionIncorporating motor imagery training into physical education classes can improve children’s visual health by enhancing cognitive and visual skills. The findings of this study may help develop interventions to prevent myopia through activation of ciliary muscles.